POSISIONING PENDIDIKAN ISLAM DI ERA GLOBALISASI - Dewantoro, Mohammad Hajar (Universitas Ahmad Dahlan, 2014)
Opportunities and challenges of globalization requires a superior human resources and competitively, which needs to be responded positively by the Islamic education. These opportunities need to be met by utilizing all the positive potential of globalization, disseminating the values of Islam to the world as an attempt to save mankind from viruses skularisasi who ignore the spiritual dimension in man. In addition, Islamic education should develop spiritual-based education vigorously supported by teachers, learners and educational organizations full support prophetic transformational leadership.